Networks for service-oriented architecture the impact of web services on wide-area networks. - Mullaley, Michael
The widespread adoption of distributed computing has been prognosticated for many years. Finally, a critical mass has been created of both enabling and demand trends that will ultimately realize the promised wave of distributed computing applications. This wave of distributed computing will have a profound impact on businesses and government agencies in many ways-and one area that will be particularly affected is wide-area networks (WAN).